Early detection of oral cancers: current status and future prospects. Issue 2 (April 2016) - Iyer, Subramania; Thankappan, Krishnakumar; Balasubramanian, Deepak
Abstract : Purpose of review: This article reviews the current literature and summarizes the latest developments in screening and early detection of oral cancers and looks at the future possibilities. Recent findings: Oral cancer is the best model for screening and prevention. The screening for oral cancer can be population based, opportunistic, or targeted. A long-term 15-year follow-up data of a randomized controlled study from a developing country setting indicated a sustained reduction in oral cancer mortality in high-risk individuals. Visual oral examination remains the mainstay in the screening. Several adjunctive techniques have been described to aid in the clinical examination of these lesions. A Cochrane review revealed that there is no evidence to recommend these adjuncts in clinically visible lesions. Salivary biomarkers seem to be promising as a tool for screening in the future. A Targeted Evidence Update for the US Preventive Services Task Force found no evidence on screening either in the general or selected high-risk population for oral cancer in the United States or on benefit of any adjunctive device affecting the performance of the screening examination. Summary: Current evidence shows that community based screening has a value in reducing the oral cancer mortality in high-risk group of population. But this evidence may not be universally applicable.